Nursing students' personality (Temperament and Character), burnout symptoms, and health and well-being - Danilo Garcia; Maryam Kazemitabar; Elina Björk; Thiago Medeiros da Costa Daniele; Marko Mihailovic; Kevin M. Cloninger; Mirna Albuquerque Frota; C.Robert Cloninger (Elsevier, 2024)
Background: About 9 million nurses will be needed by 2030. To face these unprecedented times, governments/institutions focus on educating as many nursing students as possible. This strategy is clouded by burnout and lack of both health and well-being among students and by the fact that personality is one of the major determinants of these health outcomes. Nevertheless, recent findings show that personality is a complex adaptive system (i,e., nonlinear) and that combinations of people's temperament and character traits (i.e., joint personality networks) might provide further information to understand its development, academic burnout, and lack of health and well-being. Aims: Our aims were to investigate the linear relationship between nursing students' personality, burnout, health, and well-being; investigate the linear mediational effects of personality and burnout on health and well-being; and investigate differences in these health outcomes between/within students with distinct joint personality networks (i.e., nonlinear relationships). Method: Swedish nursing students (189 women, 29 men) responded to the Temperament and Character Inventory, The Maslach Burnout Inventory-General Survey for Students, and the Public Health Surveillance Well-Being Scale. We conducted correlation analyses and Structural Equation Modeling and, for the nonlinear relationships, Latent Profile Analysis and Latent Class Analysis for clustering and then Analyses of Variance for differences in health outcomes between/within students with distinct personality networks. This study was not pre-registered. Results: High levels of health and well-being and low burnout symptoms (low Emotional Exhaustion, low Cynicism, and high Academic Efficacy) were associated with low Harm Avoidance and high Self-Directedness. Some personality traits were associated with specific health outcomes (e.g., high Self-Transcendence-high Emotional Exhaustion and high Persistence-high Academic Efficacy) and their effects on health and well-being were mediated by specific burnout symptoms. Cynicism and Emotional Exhaustion predicted low levels of health and well-being, Academic Efficacy predicted high levels, and Cynicism lead both directly and indirectly to low levels of health and well-being through Emotional Exhaustion. We found two joint personality networks: students with an Organized/Reliable combination who reported being less emotionally exhausted by their studies, less cynical towards education, higher self-efficacy regarding their academic work/skills, and better health and well-being compared to nursing students with an Emotional/Unreliable combination. Conclusions: The coherence of temperament-character, rather than single traits, seems to determine students' health outcomes. Thus, nursing education might need to focus on helping students to develop professional skills and health-related abilities (e.g., self-acceptance and spiritual-acceptance), by supporting self-awareness.